Comparison of the Effectiveness Between Preoperative Ibuprofen and Naproxen for Pain Control after Orthodontic Archwire Placement (Journal of Dentistry and Allied Science, 2023)
Background: Orthodontic procedures like separator placement, archwire placement, and activation, application of orthopedic forces, and debonding cause pain in patients. Researchers showed that the administration of preoperative NSAIDs reduces the pain that patients commonly experience during archwire placement. Purpose: This quasi-experimental study evaluates the efficacy of naproxen and ibuprofen as preoperative analgesics. Method: Selected 56 cases were divided into two groups. Ibuprofen and Naproxen were administered one hour before archwire placement, and their pain level was recorded in a pre-developed 100 mm visual Analogue Scale for chewing, biting, fitting front teeth, and fitting back teeth together at different time points after archwire placement. A quasi-experimental study was performed. Result: The patients who took Naproxen (500mg) preoperatively felt significantly less pain than Ibuprofen (400 mg) at 6, 12, 24, 48, and 72 hours in chewing food, only at 24 hours for biting food while for fitting back teeth at 6, 12 hours and seven days and for fitting front teeth at 24 and 72 hours. The pain in chewing and biting was found to be quite similar, except that there were no differences in pain scores between the two experimental groups at two hours. In both treatments, female participants had a lower pain level than men. In addition, it was found that there is an additional need for one or two post-operative analgesics for complete pain relief. Conclusions: Naproxen (500 mg) is more effective than ibuprofen (400 mg) for decreasing the severity of pain during archwire placement.Journal of Dentistry and Allied Science, Vol. 6 No 2: 8-18